Adaptive cooperative output regulation of polytopic systems via spectrum estimation: An H∞ perspective. (May 2023) - Fu, Chengcheng; Zhang, Hao; Huang, Chao; Wang, Zhuping; Yan, Huaicheng
Abstract: This paper focuses on the fully distributed robust cooperative output regulation of polytopic multi-agent systems. Based on the internal model principle, the problem being studied is first converted into a stabilization problem of interconnected systems without external disturbance. Next, small-gain conditions are characterized to obtain an equivalent H ∞ problem, where the upper bound of the H ∞ performance index is closely associated with the spectral radius of the communication topology correlation matrix. To design adaptive fully distributed control protocols in both state and output feedback settings, a finite-time observer and a topology information estimation algorithm are proposed to avoid global information. Compared with existing related works, our methods do not require global information a priori. Finally, the proposed methodology is applied to numerical and practical examples of multi-pendulum systems to demonstrate the feasibility and applicability of the theoretical results.